Efeito protetor da proteína anti-inflamatória Galectina-1 sobre o processo de uveíte induzida pelo inflamógeno lipopolissacarídeo - Zanon, Caroline de Freitas [UNESP] (2014)
Inflammation is the main contributing factor for many eye disorders, and may lead to blindness and, in general, glucocorticoids are the drugs frequently administered. However, the side effects of these drugs limit their use. Endogenous protein galectin-1 (Gal-1) is able to control the process of apoptosis and transmigration of leukocytes, contributing to the homeostasis of inflammation. However, the expression of Gal-1 in normal and inflamed ocular tissues has been little studied. Investigate, in vivo, the expression and mechanism of action of endogenous protein Gal-1 in ocular tissues of rats in endotoxin-induced uveitis (EIU), and anti-inflammatory effect of administration of recombinant galectin-1 (rGal-1). Male rats (Rattus norvegicus) were anesthetized and inoculated in the right footpad with lipopolysaccharide (LPS) (1mg/kg) for developing uveitis, and after it divided into the following experimental groups (n=12/group): EIU 24 and 48h; EIU for 24h and treated intraperitoneally with rGal-1 (3μg/animal), 15 minutes after LPS. Blood was collected for detecting the percentage of positive cells for the adhesion molecules L-selectin (CD62L) and β2-integrin (CD11b) in polymorphonuclear leukocytes (PMNs), by flow cytometry. Inflammatory cells was quantified in aqueous humor (AqH) in the Neubauer chamber. After enucleation, the eyes were processed for histopathological analysis, dosage levels of MCP-1, IL-1β, TNF-α, IL-6 and IL-10 cytokine by panels Milliplex MAP and analysis of the expression of endogenous Gal-1 by immunohistochemistry and Western blotting. EIU 24h provoked expected signals of inflammation, including intense recruitment of neutrophils (Nɸs) in ocular tissues, AqH and blood, and release of proinflammatory cytokines. Treatment with rGal-1 attenuated the effects occurring in the EIU by inhibiting the infiltration of Nɸs in eye tissues and the AqH, percentage decreased of CD62L+ cells and, also, suppressing the ...